Stress Behavior Of Tailor-Welded Blanks For Dissimilar Metals Using Finite Element Method - L. C., Wor; M. M., Rahman (Universiti Malaysia Pahang, 2015)
This paper presents the stress behavior of tailor-welded blanks (TWBs) for dissimilar metals and identifies the critical locations using the finite element method. By using dissimilar metals with different welding configurations, the critical points where the force is concentrated and the maximum forces that are exerted at those particular points can be estimated. To overcome these issues, simulation using the finite element method is used to estimate the critical point of the TWBs. Steel and aluminum are considered as welding materials. The welding parameters of current, voltage and welding velocity are modified to analyze the effect on the welding part. The different TWB configurations are the L-shape, the T-shape and the plate. Goldak’s double ellipsoid source model is used as the heat source in the investigation. The distortion of the plate increases when the power of the laser increases. The distortion is due to the residual stress caused by heating when welding. The residual stress relieved during cooling makes the plate distort. It can be seen that the increase in power increases the temperature since power is the energy source conducting heat to the plate. Thus, the temperature is proportional to the power used. The heat-affected zone increases during the welding process when the power increases. Increasing the power also increases the TWB distortion.